Synthesis of a New Series of Anthraquinone-Linked Cyclopentanone Derivatives: Investigating the Antioxidant, Antibacterial, Cytotoxic and Tyrosinase Inhibitory Activities of the Mushroom Tyrosinase Enzyme Using Molecular Docking - Mullaivendhan J; Akbar I; Ahamed A; Gatasheh MK; Hatamleh AA; Raman G; Manilal A; Kuzhunellil Raghavanpillai S (Dove Medical Press, 2024)
Janani Mullaivendhan,1 Idhayadhulla Akbar,1 Anis Ahamed,2 Mansour K Gatasheh,3 Ashraf Atef Hatamleh,2 Gurusamy Raman,4 Aseer Manilal,5 Sabu Kuzhunellil Raghavanpillai6 1Research Department of Chemistry, Nehru Memorial College (Affiliated to Bharathidasan University), Puthanampatti, Tamil Nadu, 621007, India; 2Department of Botany and Microbiology, College of Science, King Saud University, Riyadh, 11451, Saudi Arabia; 3Department of Biochemistry, College of Science, King Saud University, Riyadh, 11451, Saudi Arabia; 4Department of Life Science, Yeungnam University, Gyeongsan, Gyeongbuk-do, 38541, South Korea; 5Department of Laboratory Sciences, College of Medicine and Health Sciences, Arba Minch University, Arba Minch, Ethiopia; 6Biogeochemistry Division, VM Clays and Minerals, Thiruvananthapuram, Kerala, IndiaCorrespondence: Aseer Manilal; Idhayadhulla Akbar, Email aseer.manila@amu.edu.et; a.idhayadhulla@gmail.comPurpose: New bioactive anthraquinone derivatives are investigated for antibacterial, tyrosinase inhibitory, antioxidant cytotoxic activity, and molecular docking.Methods: The compounds were produced using the grindstone method, yielding 69 to 89%. These compounds were analyzed using IR, 1H, and 13C NMR and elemental and mass spectral methods. Additionally, the antibacterial, antioxidant, and tyrosinase inhibitory activities of all the synthesised compounds were evaluated.Results: Compound 2 showed remarkable tyrosinase inhibition activity, with an (IC50: 13.45 μg/mL), compared to kojic acid (IC50: 19.40 μg/mL). It also exhibited moderate antioxidant and antibacterial activities with respect to the references BHT and ampicillin, respectively. Kinetic analysis revealed that the tyrosinase inhibitory activity of compound 2 was non-competitive and competitive, whereas that of compound 1 was low. All compounds (1-8) were significantly less active than doxorubicin (LC50: 0.74± 0.01μg/mL). However, compound 2 affinity for the 2Y9X protein was lower than kojic acid, with a lower docking score (− 8.6 kcal/mol compared to (− 4.7 kcal/mol), making it more effective.Conclusion: All synthesized compounds displayed remarkable antibacterial, tyrosinase inhibitory, antioxidant, and cytotoxic activities, with compound 2 showing exceptional potency as a multitarget agent. Anthraquinone substituent groups may offer the potential for the development of treatments. The derivatives were synthesized using the grindstone method, and their antibacterial, antioxidant, tyrosinase inhibitory, and cytotoxic activities were inspected. Molecular docking and molecular dynamics simulations were performed using compound 2 and kojic acid to validate the results and confirm the stability of the compounds.Keywords: anthraquinone, tyrosinase enzyme, antioxidant activity, molecular docking, binding affinity, kojic acid, antibacterial activity, cytotoxic activity